Experimental study on natural convection from vertical cylinders with perforated plate fins - Shin, Hyun Soo; Kim, Dong Kwon (Applied Thermal Engineering, 2024)
In this short communication, an experimental investigation on vertical cylinders with perforated plate fins under natural convection is conducted using sixteen finned cylinders of different configurations. Experiments are carried out to measure the heat dissipation from perforated-finned cylinders for various perforation diameters, fin numbers, and temperature differences between the base and surroundings. Based on the experimental results, correlations to predict the Nusselt number are proposed. Utilizing the proposed correlation, a thermal model capable of predicting the thermal performance of the perforated-finned cylinder with a prediction error within 10% is developed. By applying this thermal model, it is shown that the thermal performance of vertical cylinders with plate fins can be improved by 13% through perforation.
Keywords: Experimental investigations; Fin numbers; Fin temperature; Finned cylinder; Perforated plate fin; Plate fins; Temperature differences; Thermal model; Thermal Performance; Vertical cylinders; Natural convection; Perforated plate fins; Vertical cylinders